Affordances and constraints of communities of practice to promote bilingual schooling. Issue 2 (19th February 2019) - Scanlan, Martin; Kim, Minsong; Ludlow, Larry
Abstract : Purpose: As the demographic landscape in the USA becomes more culturally and linguistically diverse (CLD), schools must build educators' professional knowledge and skills to better serve students whose mother tongues are not English. The purpose of this paper is to report on the formation of a network of schools collaboratively transforming their approaches to teaching and learning in order to meet the educational needs of this changing student population. Design/methodology/approach: To determine how relational networks in this network affect the learning of educators to implement the bilingual education model, the authors drew from three data sources: a social network survey, semi-structured interviews and archival documents. Findings: The schools in this study are engaged in a dramatic restructuring, moving from monolingual English schools to a network of two-way immersion bilingual schools. The evidence from this study revealed different information sharing structures within the relational networks. The authors found organizational structures of interactive spaces and teams supporting the relational networks that created communities of practice, and these communities of practice fostering all three aspects of profession capital (human, social and decisional). Research limitations/implications: The analysis points toward the complicated nature of organizational learning within networks of schools. While some relational networks were strong, the authors also note gaps and disconnections in the network interactions, despite the structures promoting connectivity. Hence, this study sheds light on both the power and the limitation of networked learning within and across school striving to improve the teaching and learning for CLD students. Originality/value: This original analysis lays the foundation for future investigations of networked learning.